2020
DOI: 10.3390/children7110241
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Status and Physical Activity with Lipid Profile in Korean Children and Adolescents: A Population-Based Study

Abstract: Dyslipidemia is one of the important influencing factors of cardiovascular health in the youth, and thus, assessment of its etiology is important. We aimed to investigate the association of dyslipidemia with vitamin D and physical activity in Korean children and adolescents. Data of 3183 subjects aged 12–18 years in the Korea National Health and Nutrition Examination Survey were analyzed. Participants were divided into subgroups according to sex, body mass index, 25-hydroxyvitamin D levels, and lipid profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…In a meta-analysis of eight prospective cohort study, the group with the lower 20% of serum vitamin D levels was associated with increased cardiovascular mortality and all-cause mortality (34). Vitamin D deficiency is also correlated with dyslipidemia (35) and is thought to be more influential in high-fat diets such as KDT.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of eight prospective cohort study, the group with the lower 20% of serum vitamin D levels was associated with increased cardiovascular mortality and all-cause mortality (34). Vitamin D deficiency is also correlated with dyslipidemia (35) and is thought to be more influential in high-fat diets such as KDT.…”
Section: Discussionmentioning
confidence: 99%
“…30) Another recent study of nationwide representative data of 2581 non-obese children aged 12-18 years revealed that vitamin D deficiency (serum 25[OH]D ≤20 ng/mL) was associated with low HDL-C levels but not with high TC, TG, and LDL-C levels. 31) Despite the inconsistent results for each lipid profile, most studies showed an overall positive association between serum 25 (OH) D levels and favorable lipid profiles. However, it is unclear whether vitamin D supplementation positively affects lipid profiles.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The vitamin D-deficient group (serum 25[OH]D <20 ng/mL) showed higher serum TG levels and TG/HDL-C ratio than the normal vitamin D level group [ 30 ]. Another recent study of nationwide representative data of 2,581 nonobese children aged 12–18 years revealed that vitamin D deficiency (serum 25[OH]D ≤20 ng/mL) was associated with low HDL-C levels but not with high TC, TG, and LDL-C levels [ 31 ].…”
Section: Pediatric Health Issues Associated With Lipid Profilesmentioning
confidence: 99%
“…Lipid profile and atherogenic index (AI) are important predictors of dyslipidemia, atherosclerosis, and cardiovascular disease. Any changes in normal lipid levels put people at greater risk of developing cardiovascular diseases and abnormal endothelial cell function (5).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, regular aerobic exercise plays a significant role in the prevention and control of these diseases (5). However, little is known about the preventative effect of strength training on the risk factors for cardiovascular diseases such as high blood pressure, cholesterol levels, obesity, and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%